Colloidosome like structures: self-assembly of silica microrods. Issue 32 (14th March 2016) - Datskos, P.; Polizos, G.; Bhandari, M.; Cullen, D. A.; Sharma, J.
Abstract : Self-assembly of micron-sized silica rods is demonstrated using a Pickering emulsion based strategy. Abstract : Self-assembly of one-dimensional structures is attracting a great deal of interest because assembled structures can provide better properties compared to individual building blocks. In the present work, silica microrod self-assembly has been demonstrated by exploiting Pickering emulsion based strategy. Micron-sized silica rods were synthesized employing previously reported methods based on polyvinylpyrrolidone/pentanol emulsion droplets. Rods self-assembled to make structures in the range of ≈10–40 μm. Smooth rods assembled better than segmented rods. The assembled structures were bonded by weak van der Waals forces.